Measurement of Temporal Distinction of Reducing Agricultural Areas in Ankawa Distract between 1991 and 2015 - األشخاذ اهًصاغد اهدلخْر ِاشى ٕاشٌٖ ضًدايٌٖ; األشخاذ اهًصاغد اهدلخْر هٖوٓ يطًد قّريان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Reducing the area of agricultural lands is a temporary result from urban expansion, which these days has become a problem that has been experienced by most countries; despite their spatial and temporal differences. This problem in the developing countries is associated with the excessive of population growth, in addition to the technological advancement, improving in the living conditions of population and the changes in the fields of social, political and administrative. The research aims to study and measure temporal distinction of reduction of the agricultural areas of Ankawa between the years 1991 to 2015, by using aerial images and the basic design map of Ankawa. Geographic Information System was used to map and measure these areas which used for inhabitation and cultivation purposes. The results of the study showed that arable lands had been changed and reduced with time in the district. In 1991, the district had roughly (60, 000) hectare of agricultural lands, but in 2015 the district lost all of these lands and at the same time the urban areas had doubled by (7) times. Thus, the percentage of changes had reached more than (616%). The results also showed that the urban areas on the surrounding agricultural lands were not expanded equally; rather they were extended towards east and north part of the district. Indeed, no expansion can be seen towards west and south because of having some humanitarian obstacles such as Erbil International Airport and (100) metre street which separates it from Erbil city. The study also refers to the factors of decreasing agricultural lands and the way of confronting and measuring the rate of changing in the mentioned district in the present study.